Sistem Pemerintahan Masyarakat Hukum Adat Baduy Dalam Kerangka Sistem Otonomi Daerah - Edi Mulyadi; Eki Furqon (Ajudikasi : Jurnal Ilmu Hukum, 2021)
Customary law communities are the most important part of the history of the development of the Indonesian nation. The contribution given by the customary law community since ancient times has been very large for the development of human civilization, especially in the aspect of order that exists in customary law. The Baduy tribe is one of the customary law communities whose existence is still maintained to this day. The Baduy customary law community has a legal system including its government system which is the hallmark of indigenous peoples. In addition to using their customary government system, Baduy as well as part of the Unitary State of the Republic of Indonesia must participate in every national policy, especially in the area of ​​regional and village government. The recognition given by the 1945 Constitution of the Republic of Indonesia to indigenous peoples in Indonesia is the basis for the use of their respective customary law systems. Therefore, the researcher considers it necessary to conduct a study to see how the current system of governance of the Baduy customary law community is related to the existing positive law. The research method used is a normative juridical and empirical (mixed) juridical research method to see how the normative arrangements regarding the position of the Baduy community government system are and can describe what the government system is like. The specific target to be achieved in this research is to contribute ideas to the local government and the Baduy indigenous people in terms of the position of the Baduy customary government system in terms of the existing positive law. The results of the research carried out explain the Baduy customary law community uses a government system that originates from their customary law known as pikukuh or karuhun. Law 23/2014 on Regional Government gives authority to provincial and district governments to regulate the empowerment of indigenous peoples and the arrangement of customary villages through existing traditional institutions. This happens because community and village empowerment is included in the mandatory concurrent government affairs that are not related to basic services.